2005
DOI: 10.1016/j.femsim.2004.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Detection of periodontal pathogenPorphyromonas gingivalisby loop-mediated isothermal amplification method

Abstract: A method for nucleic acid amplification, loop-mediated isothermal amplification (LAMP) was employed to develop a rapid and simple detection system for periodontal pathogen, Porphyromonas gingivalis. A set of six primers was designed by targeting the 16S ribosomal RNA gene. By the detection system, target DNA was amplified and visualized on agarose gel within 30 min under isothermal condition at 64 degrees C with a detection limit of 20 cells of P. gingivalis. Without gel electrophoresis, the LAMP amplicon was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 27 publications
(54 reference statements)
3
43
0
Order By: Relevance
“…Compared to a standard PCR protocol, LAMP requires a single bath at a constant temperature instead of a thermal cycler. The performances of LAMP-and PCR-based diagnostic systems, including real-time technologies (23,40), have been extensively compared. In general, LAMP was found to be either similar or superior to PCR, and more specific (e.g., 8,13,15), but a few studies proved otherwise, such as those reported by Kato et al (18), who showed that although LAMP was 10-fold more sensitive than standard PCR for the detection of the Clostridium difficile toxin B gene (tcdB), an optimized nested-PCR assay performed much better than LAMP.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to a standard PCR protocol, LAMP requires a single bath at a constant temperature instead of a thermal cycler. The performances of LAMP-and PCR-based diagnostic systems, including real-time technologies (23,40), have been extensively compared. In general, LAMP was found to be either similar or superior to PCR, and more specific (e.g., 8,13,15), but a few studies proved otherwise, such as those reported by Kato et al (18), who showed that although LAMP was 10-fold more sensitive than standard PCR for the detection of the Clostridium difficile toxin B gene (tcdB), an optimized nested-PCR assay performed much better than LAMP.…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori occurs beneath the mucus layer, predominantly in the antrum (34). Infection is generally confirmed by histology (21), culturing (13), and the rapid urease test (RUT) (23) performed on endoscopic gastric mucosal biopsy samples or by the urea breath test (14). This latter test is a noninvasive method that detects 13 CO 2 generated by H. pylori urease (5); because it is indirect, however, it does not allow the measurement of antibiotic susceptibility, a disadvantage given that the recent gradual increase in the number of antibiotic-resistant strains has mandated susceptibility testing before eradication therapy (9,25).…”
mentioning
confidence: 99%
“…The principle of LAMP involves autocycling strand displacement DNA synthesis using a DNA polymerase with high strand displacement activity. Recent reports demonstrating the usefulness of LAMP in detecting various bacteria and viruses (10,16,17,21,27,28,32,35,37) suggested it may be useful for the rapid detection of H. pylori. The LAMP procedure is simple, and its selectivity is extremely high owing to its use of four primers that recognize six distinct regions of the target DNA.…”
mentioning
confidence: 99%
“…Although the LAMP assay required only 4 primers, 2 outer and 2 inner, that recognise 6 different regions of the target sequence (Notomi et al 2000), addition of 2 loop primers was found to enhance and accelerate the reaction, and increase not only the sensitivity but also the specificity of the assay. The 6 primers recognised 8 distinct regions of the target DNA, which minimised the probability of false positive results (Nagamine et al 2002, Maeda et al 2005. Although the LAMP assay could detect T. contejeani DNA in as little as 25 min (Fig.…”
Section: Discussionmentioning
confidence: 99%